Precipitation process for combined impurity removal from a magnesium sulphate-based leachate of ionic rare earth ore. (November 2022) - Luo, Xianping; Yuan, Xianqiang; He, Kunzhong; Zhang, Yongbing; Luo, Caigui; Liu, Zishuai; Zhou, Hepeng
Highlights: NaOH + ATA was the first time used in an ionic rare earth leaching solution. No ammonia nitrogen was caused when CaO crystallization process used. NaOH + ATA has a higher efficiency impurity removal effect than NH4 HCO3 . CaO used could obtained a better rare earth crystallization than NH4 HCO3 . This process has a certain promote effect of the growth of rare earth ions. Abstract: Impurity metal ions in ionic rare earth ores are similar to rare earth ions in terms of occurrences and similarities in properties. During the leaching operation, a large number of impurity ions enter the rare earth leaching solution, which makes the crystal form of the rare earth unstable or forms an amorphous flocculent precipitate. The commonly used ammonium bicarbonate (NH4 HCO3 ) precipitation crystallization process has low rare earth precipitation rate, long precipitation crystallization period, and high ammonia nitrogen content in precipitation wastewater. In this paper, the leaching solution obtained by ionic rare earth ore magnesium salt leaching-combined impurity removal process was taken as the research object, and the effects of precipitants, such as NH4 HCO3, calcium oxide, sodium carbonate, and oxalic acid, on the preparation of crystalline rare earth precipitation were investigated through comparison. On the premise of determining the best rare earth precipitant, the effects of dosage, stirring speed, stirring time, and aging time on the preparation of crystalline rare earth precipitate were investigated further. The precipitation effects of different precipitation processes were studied systematically combined with SEM-EDS, laser particle size analysis, and other means to characterize the morphology of crystalline products. Results showed that when calcium oxide was used as a precipitant, the molar ratio was 2.5. After stirring at a constant speed of 200 r/min for 4 h and aging for 4 h, precipitates with good crystal appearance, smooth crystal surface and easy filtration were obtained. This process promoted crystal growth of rare earth precipitates, and the crystal grain size, which was beneficial to the improvement of the quality of rare earth products, increases significantly.